El exorno artístico renacentista del monasterio del Santo Sepulcro de Zaragoza y la iglesia de San Nicolás de Bari: The Renaissance artistic decoration of the Monastery of the Holy Sepulchre in Saragossa and the Church of Saint Nicholas of Bari - Tarifa Castilla, María Josefa (Artigrama, 2025)
ResumenEl monasterio medieval del Santo Sepulcro de Zaragoza fue engalanado a lo largo del siglo XVI con un relevante conjunto de obras renacentistas, como retablos, esculturas o pinturas, a las que dedicamos el presente texto. El hallazgo de documentación inédita ha permitido profundizar en su estudio, como sucede con el contrato del desaparecido retablo mayor de la iglesia de San Nicolás de Bari ejecutado por Gil Morlanes el Joven (1526).AbstractThe medieval monastery of the Holy Sepulchre in Zaragoza was decorated throughout the 16th century with a relevant collection of Renaissance works, such as altarpieces, sculptures or paintings, to which we dedicate this text. The discovery of unpublished documentation has allowed to deepen into its study, as it happens with the contract of the disappeared main altarpiece of the church of San Nicolás de Bari executed by Gil Morlanes the Young (1526).KeywordsHoly Sepulchre, Saragossa, Renaissance, XVI Century, Gil Morlanes the Young, Sculpture, Painting.